Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/jacs.6b09471
|View full text |Cite
|
Sign up to set email alerts
|

Small Details Matter: The 2′-Hydroxyl as a Conformational Switch in RNA

Abstract: While DNA is mostly a primary carrier of genetic information and displays a regular duplex structure, RNA can form very complicated and conserved 3D structures displaying a large variety of functions, such as being an intermediary carrier of the genetic information, translating such information into the protein machinery of the cell, or even acting as a chemical catalyst. At the base of such functional diversity is the subtle balance between different backbone, nucleobase, and ribose conformations, finely regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 51 publications
(91 reference statements)
1
19
0
Order By: Relevance
“… 150 Bergonzo et al showed that using the larger, less hydrophilic phosphate groups described by these parameters yielded a better description of tetranucleotides 126 and tetraloops. 139 The Steinbrecher phosphate parameters were also used by Darré et al 151 in a different way, in conjunction with abandoning the Lorentz–Berthelot combination rules for the Lennard-Jones potential. The simulations showed a slightly better description of tetranucleotides than reported by Bergonzo et al 139 In addition, Darré et al modified also the torsional parameters of the C2′–OH group of ribose.…”
Section: Molecular Dynamics Simulation Methodologiesmentioning
confidence: 99%
“… 150 Bergonzo et al showed that using the larger, less hydrophilic phosphate groups described by these parameters yielded a better description of tetranucleotides 126 and tetraloops. 139 The Steinbrecher phosphate parameters were also used by Darré et al 151 in a different way, in conjunction with abandoning the Lorentz–Berthelot combination rules for the Lennard-Jones potential. The simulations showed a slightly better description of tetranucleotides than reported by Bergonzo et al 139 In addition, Darré et al modified also the torsional parameters of the C2′–OH group of ribose.…”
Section: Molecular Dynamics Simulation Methodologiesmentioning
confidence: 99%
“…These observations indicate that parameters related to sugar pucker and the 2 0 -hydroxyl orientation may require some refinement to better capture these effects, which are known to be coupled. [108] Stability of dsDNA using the updated Drude-2017 force field…”
Section: Simulations Of Large Rna With Complex Tertiary Structuresmentioning
confidence: 99%
“…Labeling sites must be chosen so as to avoid influencing interactions between the RNA and its binding partner(s), or perturbing secondary or tertiary interactions within the RNA or its conformational dynamics (Al-Hashimi and Walter 2008;Mustoe et al 2014;Darre et al 2016). For example, 2 ′ modifications on the ribose sugar can alter the thermal stability of double-stranded regions (Hendrix et al 1995;Fauster et al 2012), whereas attachment of fluorophores at 5 ′ or 3 ′ termini can increase duplex stability through stacking of the fluorophores on the terminal base-pairs (Cisse et al 2012;Liu and Lilley 2017).…”
Section: Labeling Rna Componentsmentioning
confidence: 99%